2021
DOI: 10.3389/fped.2021.651487
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Features of Pediatric Interstitial Pneumonia Due to Mycoplasma pneumoniae

Abstract: Background: Inflammatory response, oxidative stress, and immunologic mechanism are involved in the pathogenesis of Mycoplasma pneumoniae pneumonia (MPP). However, the role of immune system of pediatric interstitial pneumonia due to M. pneumoniae infections remains poorly understood. The aim of this study was to analyze the immunologic features of pediatric interstitial pneumonia due to Mycoplasma pneumoniae (M. pneumoniae).Methods: A retrospective study was conducted on a primary cohort of children with MPP. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“… 25 Some studies have reported that CD3 + and CD4 + T-cell counts are significantly decreased and CD8 + T-cell counts are increased in the acute phase of MP infection. 26 , 27 Therefore, it is important to monitor T-lymphocyte subsets to elucidate the efficacy and prognosis of MP infection. In the present study, we identified that, in the two patient groups with MP infection, CD4 + T-cell counts significantly increased after treatment compared with those before treatment; on the other hand, CD8 + T-cell counts significantly decreased, with more pronounced effects in the treatment group than in the control group, implying that Sangju cough mixture improved the immune system of patients with MP infection.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Some studies have reported that CD3 + and CD4 + T-cell counts are significantly decreased and CD8 + T-cell counts are increased in the acute phase of MP infection. 26 , 27 Therefore, it is important to monitor T-lymphocyte subsets to elucidate the efficacy and prognosis of MP infection. In the present study, we identified that, in the two patient groups with MP infection, CD4 + T-cell counts significantly increased after treatment compared with those before treatment; on the other hand, CD8 + T-cell counts significantly decreased, with more pronounced effects in the treatment group than in the control group, implying that Sangju cough mixture improved the immune system of patients with MP infection.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant pathological manifestation of pediatric MPP is interstitial pneumonia. In mild cases, in ammatory cell in ltration occurs within the alveolar cavities, while in severe cases, there is substantial exudation of in ammatory cells and brin into the alveolar cavities and alveolar walls, accompanied by thickening and edema of the alveolar walls [14] . The LUS ndings of the children in this study were congruent with the pathophysiological process of MPP.…”
Section: Discussionmentioning
confidence: 99%
“…When MP enters the body, it activates the body to produce pro- and anti-inflammatory cytokines, and the interaction between the two can affect the occurrence and development of the inflammatory response in the body. The body can produce pro-inflammatory cytokines such as IL-4, IL-17, TNF-α, and TGF-β to promote tissue repair by clearing pathogens; the body can also produce anti-inflammatory cytokines such as IL-10 to downregulate the body’s immune response and inhibit the overexpression of pro-inflammatory cytokines, thereby controlling the body’s inflammatory response and reducing the damage caused by pathogens 18 .…”
Section: Discussionmentioning
confidence: 99%